Pengelolaan Bahan Pustaka di Perpustakaan Kantor Camat Koto XI Tarusan Kabupaten Pesisir Selatan - Rizal, Andra; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper focuses on the management of library materials in the Library of the Office of Head Koto XI Tarusan Pesisir Selatan. The objectives are: (1) describe how the management of library materials in the library of the Office of Head Koto XI Tarusan Pesisir Selatan, (2) describing the constraints in the management of library materials in the Library of the Office of Head Koto XI Tarusan Pesisir Selatan. The method used in this paper is the writer's descriptive method. Data was collected through observation and interview techniques. Carried observation techniques to determine how the management of library materials in the Library of the Office of Head Koto XI TarusanÂ Pesisir Selatan. Based on the data analysis and discussion, it can be concluded that the management of library materials in the Library of the Office of Head Koto XI Tarusan Pesisir Selatan prepared a book for more than one book inventory ledger in order to more optimal inventory process, inventory of library materials should be done so that information about the data computerized staistik library collections can be protected in the event of damage to what the parent book, the addition of library personnel to improve the performance of the work, should add a collection of library materials are more varied. Keywords: library materials; Â library collections; management of library